2022
DOI: 10.3390/ma15155168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Process Ultrasonic Vibration on Weld Formation and Grain Size of Wire and Arc Additive Manufactured Parts

Abstract: Wire and arc additive manufacturing (WAAM) is a competitive technique, which enables the fabrication of medium and large metallic components. However, due to the presence of coarse columnar grains in the additively manufactured parts, the resultant mechanical properties will be reduced, which limits the application of WAAM processes in the engineering fields. Grain refinement and improved mechanical properties can be achieved by introducing ultrasonic vibration. Herein, we applied ultrasonic vibration to the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Additionally, to provide a comprehensive comparison between the parts processed under different conditions and to understand the impact of coupled fields on their microstructures, some other samples were also prepared under the conditions of gravity casting, single extrusion pressure, and ultrasonic casting. [20], the metallographic samples were removed from position A, as shown in Figure 1. In this way, the performance of the process under different coupling parameters could be better studied.…”
Section: Experimental Factors Materials and Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to provide a comprehensive comparison between the parts processed under different conditions and to understand the impact of coupled fields on their microstructures, some other samples were also prepared under the conditions of gravity casting, single extrusion pressure, and ultrasonic casting. [20], the metallographic samples were removed from position A, as shown in Figure 1. In this way, the performance of the process under different coupling parameters could be better studied.…”
Section: Experimental Factors Materials and Machinesmentioning
confidence: 99%
“…The obtained sample was cut into a size of Φ12 mm × 10 mm. Given that the effects of cavitation and acoustic flow under the ultrasonic vibration are more significant in the local area near the end face of the variable amplitude rod [20], the metallographic samples were removed from position A, as shown in Figure 1. In this way, the performance of the process under different coupling parameters could be better studied.…”
Section: Experimental Factors Materials and Machinesmentioning
confidence: 99%
“…A study on tungsten inert gas (TIG) and MIG welding with ultrasonic for aluminum alloys revealed that the welding material is refined, porosity reduced, unmixed zones completely eliminated, leading to the enhancement of corrosion resistance in welds [3]. These advantages are related to the introduction of a high-intensity ultrasonic field, which generates two nonlinear effects: cavitation and acoustic streaming [4]. The effects caused by ultrasonic vibrations have mixed materials at the interface between phases in the weld pool.…”
Section: Introductionmentioning
confidence: 99%